Índice de competitividad municipal 2013: Metodología para su construcción basada en análisis factorial y su aplicación en municipios urbanos en México - Sylvia Beatriz Guillermo Peón; Israel Gerardo García Pérez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
– This paper presents a detailed explanation of the methodology to construct the Municipal Competitiveness Index 2013 for Mexico. The index is calculated using a methodology based on Factor Analysis and compares the performance of 96 municipalities belonging to 24 metropolitan areas in different States of the Mexican Republic. The index includes 61 variables grouped into four dimensions or sub-indexes: Economic, Institutional, Sociodemographic and Urban-environmental. The Municipal Competitiveness Index is the average of the four indexes. The results show evidence that municipalities of Monterrey metropolitan area are, in general, the ones with higher position in the competitiveness ranking, and highlight the need of inter-municipal cooperation and coordination in order to improve competitiveness of those municipalities belonging to a common metropolitan area. The study particularly focuses on the analysis of factors of each competitiveness dimension for municipalities in Puebla State included in the sample.
Keywords: H80; R00; C40; 330; municipal competitiveness index; municipal competitiveness in Mexico; factor analysis